2015
DOI: 10.3174/ajnr.a4602
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Interhypothalamic Adhesions in Children

Abstract: SUMMARY:With the use of high-resolution MR imaging techniques, we have increasingly observed anomalies of the hypothalamus characterized by a band of tissue spanning the third ventricle between the hypothalami, often without associated clinical sequelae. Historically, hypothalamic anomalies are highly associated with symptoms referable to a hypothalamic hamartoma, midline congenital disorder, hypothalamic-pituitary dysfunction, or seizures, with very few asymptomatic patients reported. The interhypothalamic ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…1 We agree with the main message of the article: Referable hypothalamicpituitary axis symptoms are rare in patients with interhypothalamic adhesions. However, because symptoms can be present on occasion, it is prudent to exclude endocrinopathy on clinical grounds.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…1 We agree with the main message of the article: Referable hypothalamicpituitary axis symptoms are rare in patients with interhypothalamic adhesions. However, because symptoms can be present on occasion, it is prudent to exclude endocrinopathy on clinical grounds.…”
supporting
confidence: 75%
“…[2][3][4] Indeed, review of Fig 1 demonstrates sub-tle midline anomalies not mentioned in the article, including hypogenesis or volume loss of the splenium (Figs 1A and E) and a partially fenestrated, persistent cavum septum pellucidum ( Fig 1D). 1 In normal brains, the callosal splenium is typically equal to or larger in caliber than the genu. While a cavum septum pellucidum is a normal variation, it is uncommon in the general population beyond the neonatal period.…”
mentioning
confidence: 99%
“…They are less frequently described and are rarely associated with midline developmental abnormalities, as shown by the very small number of cases reported to date. The underlying etiology of IHA remains unclear, but it has been suggested that IHA results from incomplete hypothalamus cleavage, failed apoptosis or abnormal neuronal migration (28,29). Endocrine dysfunction with anterior pituitary deficiency has been reported in only three patients with IHA (29).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying etiology of IHA remains unclear, but it has been suggested that IHA results from incomplete hypothalamus cleavage, failed apoptosis or abnormal neuronal migration (28,29). Endocrine dysfunction with anterior pituitary deficiency has been reported in only three patients with IHA (29). An association of developmental defects of the hypothalamic-pituitary area, such as septo-optic dysplasia and/or ectopic posterior pituitary, with CPP has been reported in a few cases (30,31,32), but no similar case of CPP and IHA has ever been described, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…2 The authors proposed that it may be a form fruste of holoprosencephaly, given the prevalence of midline abnormalities. Ahmed et al 3 recently reported in the AJNR that most patients with this finding are asymptomatic and that these are often incidental findings. So what is the practitioner to do with these seemingly conflicting results?…”
mentioning
confidence: 89%